Motivation and Attitude in Learning English among UiTM Students in the Northern Region of Malaysia - Bidin, Samsiah; Jusoff, Kamaruzaman; Abdul Aziz, Nurazila; Mohamad Salleh, Musdiana; Tajudin, Taniza (2009)
The purpose of this study was to describe the relationship between the students’ motivation and attitude and their English Language performance. The subjects were the part two students from three UiTM campuses in the Northern Region. The research tool used was in the form of a questionnaire. The mean scores analysis of the motivation and performance revealed that the students were more extrinsically than intrinsically motivated when learning English. However, the one-way ANOVA test showed that there is no significant difference. To test the students’ attitudes and their performance, the Spearman Rho Rank-Order Correlation Coefficient was used and the analysis revealed a significant correlation between attitude and achievement. The one-way ANOVA also showed that there is a significant difference. The mean scores was used to find out whether there is any difference between the respondents of different gender and their attitude in learning English. The results showed the existence of significant difference.